COVID-19 and concerns related to self-medication - Patil, Anant D.; Sharma, Hritika; Tetarbe, Tanusri (International Journal of Basic & Clinical Pharmacology, 2020)
The practice of self-care through self-medication is not uncommon. Self-medication is not just a problem of one country, the phenomenon is global. A systematic review has highlighted this wide spread problem. Self-medication can be based on self-belief, advice of a pharmacist or another person instead of consultation with a qualified healthcare professional. In the settings of poor access to health care services and issues related to affordability of paying for medical services, people practice self-medication as the righteous approach. Some people may consume medications without consultation of a healthcare professional citing reason of time saving. Certain drugs available as prescription medicine in one country may be available over the counter in another country. Furthermore, with digitalisation, people now have an easy access to the internet where they simply explore their symptoms and find the perceived suitable treatment for the same. Thus, the reasons and pattern of self-medications may differ based on different factors including type of population affordability, and country.